How do surgeons feel about the 'Getting it Right First Time' national audit? Results from a qualitative assessment. Issue 3 (March 2020) - Birgand, G.; Troughton, R.; Mariano, V.; Hettiaratchy, S.; Hopkins, S.; Otter, J.A.; Holmes, A.
Summary: The implementation of the national 'Getting It Right First Time' was assessed by interviewing six surgeons involved at various levels in surgical site infection (SSI) audit. The positive impacts were to create new professional collaboration, improve stakeholder engagement, and increase the profile of SSIs. One particular knowledge gap highlighted was that some participants had been unaware until that point of the criteria for diagnosing an SSI. The quality of data collected was felt to be poor due to methodological flaws. The audit was described as highly time-consuming and unsustainable if leaning on junior surgeons, without protected time and designated responsibility.